1977
DOI: 10.1037/0022-006x.45.2.267
|View full text |Cite
|
Sign up to set email alerts
|

Integrated behavior change techniques for problem drinkers in the community.

Abstract: Problem drinkers in the community were subjects in a study that evaluated the therapeutic potential of learning techniques in changing abusive drinking patterns and achieving moderation. The following procedures were studied: videotaped self-confrontation of drunken behavior, aversion training for overconsumption, discrimination training for blood alcohol concentration, alternatives training, behavior counseling, and alcohol education. All the techniques were applied to Group 1 (» = 23), the last four to Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…With regard to problem drinkers, findings have been mixed. Several investigators have found a modest advantage of broad-spectrum or multimodal procedures over a focused approach (Alden, 1978;Caddy & Lovibond, 1976;, whereas others have found no significant difference between minimal and more extensive approaches (Edwards et al, 1977;Miller, 1978;Miller & Taylor, 1980;Vogler et al, 1977). In two studies using random assignment, we have found no significant differences between BSCT administered by a paraprofessional therapist and BSCT offered in a self-help (bibliotherapy) format (Miller, Gribskov, & Mortell, in press;Miller & Taylor, 1980).…”
mentioning
confidence: 60%
“…With regard to problem drinkers, findings have been mixed. Several investigators have found a modest advantage of broad-spectrum or multimodal procedures over a focused approach (Alden, 1978;Caddy & Lovibond, 1976;, whereas others have found no significant difference between minimal and more extensive approaches (Edwards et al, 1977;Miller, 1978;Miller & Taylor, 1980;Vogler et al, 1977). In two studies using random assignment, we have found no significant differences between BSCT administered by a paraprofessional therapist and BSCT offered in a self-help (bibliotherapy) format (Miller, Gribskov, & Mortell, in press;Miller & Taylor, 1980).…”
mentioning
confidence: 60%
“…A combination of viewing individualized recordings of one's own intoxicated behavior, discrimination training, forms of aversive conditioning, instruction of healthy alternative activities to drinking, and behavioral counseling resulted in consummatory reduction in approximately 63% of alcoholic subjects (Vogler, Compton, & Weissbach, 1975; Vogler, Weissbach, Compton, & Martin, 1977). However, in addition to continued uncontrolled drinking episodes, the average intake at follow-up was more than 20 drinks per week, much higher than intake of moderate drinkers.…”
Section: Resultsmentioning
confidence: 99%
“…Although no definitive answer emerges, it seems safe to say that some persons have done so and apparently quite successfully. Research indicates that those who succeed in maintaining problem-free drinking tend to be individuals whose degree of alcohol problems were less severe before treatment, whereas those with more severe alcohol problems and dependence fare best with total abstinence (Armour, Polich, & Stambul, 1978;Edwards, Duckitt, Oppenheimer, Sheehan, & Taylor, 1983;Finney & Moos, 1979;Miller & Baca, 1983;Miller & Joyce, 1979;Miller, Leckman, Tinkcom, & Rubenstein, 1986;Orford, Oppenheimer, & Edwards, 1976;Polich, Armor, & Braiker, 1981;Smart, 1978;Vogler, Compton, & Weissbach, 1975;Vogler, Weissbach, Compton, & Martin, 1977).…”
Section: Discussionmentioning
confidence: 99%